Parametric Study Of Diagonal Shear Tests On Masonry Wallettes Retrofitted By Pp-Band Mesh - Sathiparan, N.; Mayorca, P.; Meguro, K. (My University, 2009)
Unreinforced masonry is one of the most used construction materials in the world. It is also unfortunately, the most vulnerable during earthquakes and large number of casualties resulted due to the collapse of this type of structures. It reveals that development of proper retrofitting technique for masonry buildings, especially existing buildings, is the main challenge to increase seismic safety in those countries. PP-band (Polypropylene band) Technology is a simple, economical and efficient retrofit method developed at International Centre for Urban Safety Engineering (Meguro Lab 2003[1]), Institute of Industrial Science, The University of Tokyo. This technology has been developed considering economical affordability and social acceptability together with technical feasibility.
Keywords: unreinforced masonry; retrofit